Metode Penerjemahan pada Buku Panduan Ponsel Xiaomi Ke Dalam Bahasa Indonesia - Taufik Afdal; Anita Candra Dewi (Kementerian Sekretariat Negara Republik Indonesia, 2026)
Technical translation plays an vital role in transferring information across languages and cultures, particularly in the context of technological devices. This study aims to analyze the translation methods employed in rendering the Xiaomi smartphone manual from English into Indonesian. Using a descriptive qualitative approach, the research examines usage instructions and technical terms analyzed based on the translation theory proposed by Peter Newmark (1988). The findings reveal that the translation of the Xiaomi manual is predominantly characterized by a combination of communicative and semantic translation methods. The communicative method is mainly used to convey instructions and usage information in a clear, natural, and easily comprehensible manner for Indonesian users. Meanwhile, the semantic method is applied to preserve contextual meaning and ensure the accuracy of technical terminology in the source text. The findings indicate that the effectiveness of technical translation relies on a balance between meaning accuracy and textual readability. By combining communicative and semantic translation methods, the translation of the Xiaomi manual succeeds in maintaining the precision of technical information while simultaneously fulfilling the comprehension needs of the target-language readers.